Double mandibular canal and triple mental foramina: Detection of multiple anatomical variations in a single patient - Costa, Eliana Dantas [UNESP]; Peyneau, Priscila Dias; Visconti, Maria Augusta; Devito, Karina Lopes; Bovi Ambrosano, Gláucia Maria; Verner, Francielle Silvestre (My University, 2019)
Having complete information about a patient’s mandibular canal and mental foramen is fundamental to performing safer procedures and avoiding intraoperative and postoperative complications. Cone beam computed tomography (CBCT) produces accurate images for the analysis of maxillomandibular bone structures and is widely used in dentistry. The aim of this study is to report a case of mandibular bifid canal associated with triple mental foramina that was revealed with CBCT images. A 45-year-old woman was referred for a CBCT scan of remaining bone quantity to assist in preoperative implant planning. The patient had reported problems related to anesthesia during extraction of the mandibular right second and third molars. Examination showed bilateral bifurcation of the mandibular canal, from the mandibular foramen to the gonial angle. In addition, exteriorization of the mandibular canal was noticed in 3 regions; that is, there were 3 distinct mental foramina. Clinicians must be aware of these anatomical variations in the mandibular region during dental procedures to avoid complications such as difficulty in obtaining anesthesia or postoperative sensory dysfunction.
Keywords: Anatomy; Cone beam computed tomography; Mandible; Mandibular nerve